Manajemen Proxy Server dan Hak Akses Internet Menggunakan SQUID di Universitas Mulia - Djumhadi, Djumhadi (METIK, 2019)
Maximum utilization of communication channels in the network is the main factor that must be considered as well as its management, both user access rights and access time provided. Safety and comfort issues are also factors that need to be considered. Squid is one of the best proxy software commonly used as a proxy caching machine for Web clients, such as HTTP, HTTPS, FTP, gopher and other similar services, with Squid also being able to reduce bandwidth consumption while speeding up response time (response time) because the page webs that have been visited do not need to be called back again, all have been stored in proxy caching, resulting in faster access times. Squid has a stack of access controls that can boost server speeds and be able to handle requests through a single I / O process. Squid works to store meta data, especially on frequently accessed objects, they are cached in RAM memory that is capable of serving DNS lookups. Object caching is nothing but a way to store / collect internet objects, such as HTTP data, HTTPS FTP, gopher, in a local system, so that it will be easier and closer for users to retrieve objects rather than having to retrieve objects from the source.